Exploring the role of gut microbiota in colorectal liver metastasis through the gut-liver axis - Liu, Qiu-Luo; Zhou, Huijie; Wang, Ziqiang; Chen, Yan (Frontiers in Cell and Developmental Biology, 2025)
Colorectal liver metastasis (CRLM) represents a major therapeutic challenge in colorectal cancer (CRC), with complex interactions between the gut microbiota and the liver tumor microenvironment (TME) playing a crucial role in disease progression via the gut-liver axis. The gut barrier serves as a gatekeeper, regulating microbial translocation, which influences liver colonization and metastasis. Through the gut-liver axis, the microbiota actively shapes the TME, where specific microbial species and their metabolites exert dual roles in immune modulation. The immunologically “cold” nature of the liver, combined with the influence of the gut microbiota on liver immunity, complicates effective immunotherapy. However, microbiota-targeted interventions present promising strategies to enhance immunotherapy outcomes by modulating the gut-liver axis. Overall, this review highlights the emerging evidence on the role of the gut microbiota in CRLM and provides insights into the molecular mechanisms driving the dynamic interactions within the gut-liver axis.